Transcriptome of the Caribbean stony coral Porites astreoides from three developmental stages. Issue 1 (December 2016) - Mansour, Tamer; Rosenthal, Joshua; Brown, C.; Roberson, Loretta
Abstract Background Porites astreoides is a ubiquitous species of coral on modern Caribbean reefs that is resistant to increasing temperatures, overfishing, and other anthropogenic impacts that have threatened most other coral species. We assembled and annotated a transcriptome from this coral using Illumina sequences from three different developmental stages collected over several years: free-swimming larvae, newly settled larvae, and adults (>10 cm in diameter). This resource will aid understanding of coral calcification, larval settlement, and host–symbiont interactions. Findings Ade novo transcriptome for theP. astreoides holobiont (coral plus algal symbiont) was assembled using 594 Mbp of raw Illumina sequencing data generated from five age-specific cDNA libraries. The new transcriptome consists of 867 255 transcript elements with an average length of 685 bases. The isolatedP. astreoides assembly consists of 129 718 transcript elements with an average length of 811 bases, and the isolatedSymbiodinium sp . assembly had 186 177 transcript elements with an average length of 1105 bases. Conclusions This contribution to coral transcriptome data provides a valuable resource for researchers studying the ontogeny of gene expression patterns within both the coral and its dinoflagellate symbiont.